Regulation of cell signaling pathways by dietary agents for cancer prevention and treatment. (October 2017) - Pandey, Manoj K.; Gupta, Subash C.; Nabavizadeh, Ali; Aggarwal, Bharat B.
Abstract: Although it is widely accepted that better food habits do play important role in cancer prevention and treatment, how dietary agents mediate their effects remains poorly understood. More than thousand different polyphenols have been identified from dietary plants. In this review, we discuss the underlying mechanism by which dietary agents can modulate a variety of cell-signaling pathways linked to cancer, including transcription factors, nuclear factor κB (NF-κB), signal transducer and activator of transcription 3 (STAT3), activator protein-1 (AP-1), β-catenin/Wnt, peroxisome proliferator activator receptor- gamma (PPAR-γ), Sonic Hedgehog, and nuclear factor erythroid 2 (Nrf2); growth factors receptors (EGFR, VEGFR, IGF1-R); protein Kinases (Ras/Raf, mTOR, PI3K, Bcr-abl and AMPK); and pro-inflammatory mediators (TNF-α, interleukins, COX-2, 5-LOX). In addition, modulation of proteasome and epigenetic changes by the dietary agents also play a major role in their ability to control cancer. Both in vitro and animal based studies support the role of dietary agents in cancer. The efficacy of dietary agents by clinical trials has also been reported. Importantly, natural agents are already in clinical trials against different kinds of cancer. Overall both in vitro and in vivo studies performed with dietary agents strongly support their role in cancer prevention. Thus, the famous quote "Let food be thy medicine and medicine be thy food" made by Hippocrates 25 centuries ago still holds good.